Angular coefficients of Z bosons produced in pp collisions at root S=8 TeV and decaying to mu(+)mu(-) as a function of transverse momentum and rapidity - (:unkn) unknown (ELSEVIER, 2015)
Measurements of the five most significant angular coefficients, A(0) through A(4), for Z bosons produced in pp collisions at root S = 8 TeV and decaying to mu(+)mu(-) are presented as a function of the transverse momentum and rapidity of the Z boson. The integrated luminosity of the dataset collected with the CMS detector at the LHC corresponds to 19.7 fb(-1). These measurements provide comprehensive information about the Z boson production mechanisms, and are compared to the QCD predictions at leading order, next-to-leading order, and next-to-next-to-leading order in perturbation theory. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Z boson production; DILEPTONS; PAIRS